Xiyanping injection combined with acitretin for psoriasis vulgaris: A systematic review and meta-analysis - Wu, Man-Ning; Zhou, Li-Jia-Ming; Zhou, Dong-Mei (Frontiers in Pharmacology, 2022)
Background: Psoriasis represents the chronic, recurrent and inflammatory disorder. The Traditional Chinese Medicine Xiyanping injection (XYP) is extensively applied in China for treating diverse inflammatory disorders, such as bronchitis, viral pneumonia or upper respiratory tract infection. XYP may offer a potential treatment for psoriasis vulgaris (PV). This study focused on analyzing whether XYP combined with acitretin was effective and safe. Methods: The present meta-analysis was carried out in line with guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This systematic review was registered in PROSPERO (CRD42022333273). Besides, relevant randomized controlled trials (RCTs) that compared XYP plus acitretin with acitretin alone for treating PV were searched from several databases from their inception till May 2022. In addition, this work utilized RevMan5.4 to conduct risk assessment as well as meta-analysis. Results: This meta-analysis selected altogether 10 RCTs including 815 subjects. Upon quality assessment, the RCTs mainly had low or unclear risk. According to our meta-analysis results, relative to acitretin monotherapy, XYP plus acitretin increased the total clinical effective rate, as evidenced by Psoriasis area and severity index score (PASI)-20, PASI-30 and PASI-60 in patients with PV (risk ratio (RR)=1.23 Z=4.87, P<0.00001, 95% confidence interval (CI): 1.13 to 1.34); RR=1.29, Z=3.89, P=0.009, 95% CI: 1.07 to 1.55; and RR=1.31, Z=3.89, P=0.0001, 95% CI: 1.14 to 1.49); the reduced levels of TNF-α, MCP-1 and RANTES, the alleviated side effects resulting from acitretin like itchiness (RR=0.54, 95%CI: 0.4 to 0.74, Z=3.94, P<0.0001), and the increased levels of aminotransferases and dyslipidemia (RR=0.5, 95%CI=0.29, 0.86, P=0.01; and RR=0.41, 95%CI=0.23, 0.75, P=0.004). Conclusion: As suggested in the present meta-analysis, XYP combined with acitretin effectively and safely treats PV.